Performance Optimization of Java Virtual Machine on Dual-Core Technology for Web Services - A Study - Mun, Chong Kam; KrishnaRao, G.S.V.R.; Lam, Hai-Shuan; Eswaran, C.; Phon-Amnuaisuk, Somnuk (2007)
How well the web applications handle the workload is a key factor in determining the performance of the web service. Due to its support for multithreading at language level, Java is becoming a popular language for web application. The performance of Java application is greatly dependent on Java Virtual Machine (JVM). Performance of multithreaded Java application can be enhanced by fully utilizing the computing resources of dual-core processor. This paper targets in optimizing the JVM to take advantage on dual-core processor. With the optimization, the web service is expected to have a marked performance gain.